Nilai Sportivitas Dalam Perkembangan Kebudayaan Masyarakat Jepang - Sri Sudarsih (KIRYOKU, 2019)
(Title: Value Of Sportivity In The Development Of Japanese Community Culture) This research is related to the development of Japanese culture. As a result, the pupose of this research is to describe the development of Japanese culture from time to time and then interpret the value of sportsmanship in the development of culture. This research is a qualitative study of philosophy. The formal object in this study is the philosophy of value, while the material object is Japanese culture. The method used is descriptions and interpretation.The results of this study are described as follows: The development of Japanese culture is formed through interaction with other nation. Japan was originally a nation that closed itself outside cultural intervention, but then the government opened itself up after realizing that there are still many left behind from other nations. Then the policy was changed by opening up to study in more development countries. The value of sportsmanship shown by Japanese people with an open mind and recognizing the superiorityof other nations and applying them in Japan according to their condition and needs. The sportsmanship of the Japanese people was able to accelerate the nation’s progress and proved that Japan was superior in various fields.